Traction on Rods within Cylinders Containing Grains: An Analogy with the Upward Movement of Trees in Tornadoes - Abel López Villa; Josué Hernández-Juárez; Abraham Medina; Ronier Diez-Barroso; Daniel Armando Serrano (Fluids)
In this work, the frictional traction forces developing in the annular space between two concentric vertical cylinders consisting of the outer surface of a cylindrical rod and the inner sidewall of a wider circular cylinder will be analyzed. The experiments carried out for this study allowed us to measure the traction on the rod for several filling heights, H. For the rod, it is possible to find a linear relation between the theoretically computed traction <semantics>Trod</semantics> and the traction measured experimentally, <semantics>TrodM</semantics>. Based on these results, it is possible to understand the fascinating phenomenon of the lifting, by the rod, of the weights of the mass of grains and of the outer cylinder. Finally, a physical analogy between this problem and the upward movement of trees in tornadoes can be identified.